Food products labeling in Georgia: problems and solutions - Gurchiani, Tamuna; Verulava, Tengiz; Jorbenadze, Revaz (International Journal of Engineering and Technology, 2019)
The Georgian legislation is a very clear regarding food labeling and completely shares the regulations and fundamental principles of all EU member states at formal level, but there are no effective mechanisms and institutions in place to react to the violation of the established regulations of the law, as well as to be responsible on the increase of public awareness, raising the food purchase and consumption culture. The aim of the thesis is to show problems in the Georgian food market in terms of fulfillment of fundamental norms envisaged under the EU Association Agreement. Qualitative research methodology - Observation method was used for data gathering. Observation was conducted in agricultural hypermarkets of Tbilisi. The situation in Georgia in terms of food labeling norms is quite complicated. The fundamental rules are met in no object of food sales, the information printed on food products creates the obscure presentation for customers regarding its content and suitability, the level of awareness of consumers is very low, consumers are not interested in details about the label information. The consumers focus on the price of products not on the information about its characteristics. Despite regulations that exists on formal level and existence of National Food Agency and also several active projects within partnership with European Union, situation in Georgia is complicated with lack of information from consumers and spurning food safety norms from their side. It is important to increase consumers awareness and actively turning them into those processes.Â